2002
DOI: 10.1097/00004647-200201000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Unchanged Cerebral Blood Flow and Oxidative Metabolism after Acclimatization to High Altitude

Abstract: The authors investigated the effect of acclimatization to high altitude on cerebral blood flow and oxidative metabolism at rest and during exercise. Nine healthy, native sea-level residents were studied 3 weeks after arrival at Chacaltaya, Bolivia (5,260 m) and after reacclimatization to sea level. Global cerebral blood flow at rest and during exercise on a bicycle ergometer was measured by the Kety-Schmidt technique. Cerebral metabolic rates of oxygen, glucose, and lactate were calculated by the Fick principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 23 publications
11
107
6
1
Order By: Relevance
“…The values obtained for CBF and CMRO 2 (and thus by consequence the derivation of L) were noticeably higher than those reported in previous studies using the same technique, although with 133 Xe as the tracer (Madsen et al, 1993;Moller et al, 2002). The reasons for this discrepancy are not clear, although we remain confident that they were not caused by the contamination of samples with blood from extracerebral regions or as a consequence of inadequate desaturation.…”
Section: Discussioncontrasting
confidence: 67%
“…The values obtained for CBF and CMRO 2 (and thus by consequence the derivation of L) were noticeably higher than those reported in previous studies using the same technique, although with 133 Xe as the tracer (Madsen et al, 1993;Moller et al, 2002). The reasons for this discrepancy are not clear, although we remain confident that they were not caused by the contamination of samples with blood from extracerebral regions or as a consequence of inadequate desaturation.…”
Section: Discussioncontrasting
confidence: 67%
“…A few other reports contradict our findings. Comparing high altitude (B11% FiO 2 ) to sea level, Moller et al, (2002) found no changes in CMRO 2 or CBF using a 133 Xe technique. Rockswold et al, (2010) studied O 2 metabolism in brain injury patients using a nitrous oxide technique and found that hyperoxia increased CMRO 2 , but Diringer et al, (2007) found no CMRO 2 changes.…”
Section: Physiological Considerationsmentioning
confidence: 77%
“…Rockswold et al, (2010) studied O 2 metabolism in brain injury patients using a nitrous oxide technique and found that hyperoxia increased CMRO 2 , but Diringer et al, (2007) found no CMRO 2 changes. Several reasons may have contributed to these discrepancies, including different species, experimental conditions as well as pathological effects (Diringer et al, 2007;Maandag et al, 2007;Moller et al, 2002;Rockswold et al, 2010). Collectively, these factors make a direct comparison virtually impossible.…”
Section: Physiological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies have reported unchanging cerebral metabolic rate of oxygen (CMRO 2 ) with severe (PaO 2~3 5 mm Hg) or moderate acute hypoxia at SL; 7 and after 3 weeks acclimatization to HA (5,260 m; PaO 2~5 1 mm Hg) in lowlanders 8 or in HA residents exposed to acute hypoxia at 3,800 m (PaO 2~4 1 mm Hg 9 ). Only one study has reported a 5% increase in CMRO 2 (using magnetic resonance imaging) during acute hypoxia roughly equivalent to 4,000 m HA (SaO 2 was not reported but was likely ~85%) 10 -this discrepancy likely reflects different methodologies and their respective assumptions.…”
Section: Introductionmentioning
confidence: 99%